Thermomechanical performance and high Brunauer-Emmett-Teller surface area of poly(vinyl alcohol)/silica/clay and poly(vinyl alcohol)/(fumed silica)/clay nanocomposites - Chang, Josephine Hui Lai; Md. Rezaur, Rahman; Sinin, Hamdan; Mahbub, Hasan; Liew, Fui Kiew; Md. Mizanu, Rahman; Md. Faruk, Hossen (Society of Plastics Engineers (SPE) t, 2017)
Poly(vinyl alcohol)/silica/clay (PVA-si-clay) and poly(vinyl alcohol)/(fumed silica)/clay (PVA-fsi-clay) nanocomposites were prepared via solution intercalation by exploiting phase separation based on the bridging of particles by polymer chains. Both nanocomposites were characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, adsorption isotherm (Brunauer-Emmett-Teller model [BET]), X-ray fluorescence, thermogravimetric analysis, and tensile testing. The Fourier-transform infrared spectroscopy indicated that the PVA-si-clay (1.28E) nanocomposite had a much broader peak compared with other nanocomposites. The PVA-si-clay (1.28E) nanocomposite contained the highest percentage of silicon group compared with other nanocomposites. According to the results of the scanning electron microscopy, clay (1.28E) showed better compatibility with the PVA-si matrix followed by clay (1.30E) with PVA-fsi matrix. The results of the Brunauer-Emmett-Teller model showed PVA-si-clay (1.28E) and PVA-fsi-clay (1.30E) nanocomposites had a higher surface area and average pore volume with a smaller pore size. The hydroxyl-functionalized PVA compatibilizer enhanced the mechanical properties as well as the thermal properties because of a higher level of interaction between the hydroxyl groups of PVA, the silanol groups of silica phase, and the modified clay.